Sakralitas Waruga: Situs Suci dan Identitas Kultural Masyarakat Minahasa - Sopacoly, Mick Mordekhai; Lattu, Izak Y. M.; Timo, Ebenhaizer I. Nuban (FIKRAH, 2019)
This article aims to explore Waruga cultural site focusing on rituals and sacredness performed by indigenous community in Minahasa. The data was obtained through interview, observation, documentary and literature studies in a qualitative manner. The community made totems as a sacred, symbols of identity and a social cohesion. This attitude was obvious when the Minahasa indigenous community held a ritual to respect their ancestors (dotu) as well as to relate to the Most High (Opo Empung). Through the rituals, the community had ties with one another and confirmed the identity of Tou Minahasa. The Waruga had a significant influence on the Minahasa indigenous community because it had noble values. Everything related to the Waruga, both ancestral spirits, burial grounds and heirloom lands were considered sacred. Therefore, the Waruga was not only an ordinary site, but also a sacred site. This study concludes that the Waruga was a totem and unifying symbol of Minahasa maintaining social solidarity.